Differential effect of nerve injury at birth on the activity pattern of reinnervated slow and fast muscles of the rat. - Navarrete, R (1984)
The activity patterns of the reinnervated slow soleus and fast extensor digitorum longus (e.d.l.) muscles were studied in rats during the first 6 months after sciatic nerve crush at birth, using chronic electromyography. When the nerve lesion was inflicted shortly after birth, the recovery of the muscle weight and size was always much less than if the same lesion was inflicted on adult animals. As previously demonstrated, this effect is due to motoneurone and muscle fibre loss. Following reinnervation after a neonatal crush, the soleus muscle recovered its normal tonic activity pattern during postural and spontaneous locomotor activity. By contrast, in the reinnervated e.d.l. muscle, abnormal tonic motor unit activity was recorded during locomotion, in addition to the phasic activity characteristic of the normal muscle. In response to postural reflexes elicited by tilting the animal, tonic motor unit activity was recorded from the reinnervated e.d.l. muscle, whereas the normal muscle was not activated by these stimuli. The aggregate activity recorded from the reinnervated e.d.l. during spontaneous locomotion was about 2-3 times greater than normal, whereas in the reinnervated soleus no significant change took place. In animals which had their nerves crushed as adults, the activity pattern and aggregate activity of both muscles was similar to normal. The firing pattern of individual motor units from normal and reinnervated muscles was compared. After a neonatal crush, the mean frequency of firing of e.d.l. motor units was significantly lower compared to normal or to that after an adult crush, whereas in soleus no significant change was found. These results indicate that peripheral nerve lesions during early development affect predominantly the development of motoneurones with a phasic, high-frequency discharge pattern resulting in a shift towards tonic, lower-frequency motor unit activity.